Three new cassane diterpenoids from the seed kernels of Caesalpinia sinensis. (February 2022) - Li, Ping; Zhang, Bao-Hui; Zhu, Zhi-Wei; Jing, Wen-Hua; Wang, Miao; Gao, Hui-Yuan
Graphical abstract: Highlights: Three undescribed cassane derivatives were isolated from Caesalpinia sinensis . Compounds 1 -3 featured an uncommon isomerized furan D-ring in cassane skeleton. All isolates were evaluated for their anti-inflammatory activities. Abstract: Three new cassane derivatives, caesall FE (1 ) and caesalminaxin HC-HD (2 -3 ), together with four known compounds (4 -7 ) were separated from the seed kernels of Caesalpinia sinensis, and their structures were elucidated by means of analysis of comprehensive spectroscopic data, especially 1D and 2D NMR and HRESIMS. Compounds 1 -3 represented the new examples of cassane diterpenoids containing an isomerized furan ring fused with an aromatized C ring or conjugated with one additional double bond. Biological evaluation revealed that compounds 1 -7 could inhibit the overproduction of NO induced by LPS, and compounds 2 and 4 -6 exhibited the inhibitory ration more than 60 % at the concentration of 50 μ M.